Analisis Kemampuan Pemecahan Masalah Matematika Siswa berdasarkan Tingkat Adversity Quotient (AQ) - Zanirah Permatasari; Nyoman Sridana; Amrullah Amrullah; Ketut Sarjana (Griya Journal of Mathematics Education and Application, 2022)
The purpose of this research was to describe the level and relationship of mathematical problem solving students based on the Adversity Quotient (AQ) level on year academic 2019/2020. The research metodology used was questionnaires, tests, and interviews. The results showed that the AQ level of 8th grade students was generally dominant at the moderate AQ level (camper), that is 23 students (71.88%) from 32 students who took the questionnaire. In solving mathematical problems according to the Polya stage, students who are at a high AQ level (climber) have moderate abilities at the stage of understand the problem, devise and carry out the plans to solve the problem, and having abilities with a low level at the stage of look back. Students at the moderate AQ level (campers) have moderate abilities at the stage of understand the problem, have good abilities at the stage of devise and carry out the plans to solve the problem, and have low levels of ability at the stage of look back. Students at a low AQ level (quitter) have moderate abilities at the stage of understand the problem, devise and carry out the plans to solve the problem, and having a low level ability at the stage of look back. Based on the Spearman rank, it was found that there was a relationship between the AQ level and the students' mathematical problem solving ability, but it was classified as very low and only had an effect of 1.21%. This is because the climbers have not been able to carry out all stages of Polya's problem solving well, the habits of students who only rely on memorizing formulas when facing math problems, and the habit of discussing when written tests take place which makes students unable to focus optimally in solving problems.